A Market Scheduling for New Normal Logistics in the Wake of Corona Virus Diseases-19 in Bandung City - Carles Sitompul; Paulina Kus Ariningsih; Fran Setiawan (Universitas Katolik Parahyangan, 2020)
Recent developments on the worldwide spread of Corona Virus Diseases-19 (COVID-19) show the vulnerability of human beings to pandemic risks in terms of biological, social, and economic factors. While human lives are the most important factor, a proposed solution dealing with pandemics should be sustainable which also includes other factors. Quarantines and physical distancing have been seen as effective ways to slow down the spread of COVID-19. We therefore propose a market scheduling model with multi-objectives to support physical distancing minimizing the number of people in a certain area in a given time (crowds) and minimizing the virus spread rates. An analytical model is proposed and solved for Bandung City. The results show some promising ideas on how to slow down the virus spread without compromising both health and economic objectives. The future potential research of the model is also presented.